2008
DOI: 10.1523/jneurosci.2377-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Reduces Vascular Amyloid-  in PDAPP Mice

Abstract: In addition to parenchymal amyloid-␤ (A␤) plaques, Alzheimer's disease (AD) is characterized by A␤ in the cerebral vasculature [cerebral amyloid angiopathy (CAA)] in the majority of patients. Recent studies investigating vascular A␤ (VA␤) in amyloid precursor protein transgenic mice have suggested that passive immunization with anti-A␤ antibodies may clear parenchymal amyloid but increase VA␤ and the incidence of microhemorrhage. However, the influences of antibody specificity and exposure levels on VA␤ and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 33 publications
5
96
0
Order By: Relevance
“…In the hippocampus, the area fraction covered with ThioS ϩ ␤-amyloid plaques in antibody-treated APP/PS1 mice was Ͼ60% lower, from 1.32 Ϯ 0.29% in vehicle-treated APP/PS1 animals to 0.48 Ϯ 0.21% ( p ϭ 0.05) in ␣-A␤-treated mice. Progressive accumulation of ␤-amyloid in the vicinity of blood vessels can result in microhemorrhages, and some studies have linked immunotherapy to an initial increase in CAA and microhemorrhages (Pfeifer et decrease during longer treatment periods (Schroeter et al, 2008). To exclude that the ␣-A␤ antibody treatment used here decreased parenchymal A␤ plaques but increased vascular A␤ deposits, we quantified CAA visualized by ThioS staining.…”
Section: Resultsmentioning
confidence: 99%
“…In the hippocampus, the area fraction covered with ThioS ϩ ␤-amyloid plaques in antibody-treated APP/PS1 mice was Ͼ60% lower, from 1.32 Ϯ 0.29% in vehicle-treated APP/PS1 animals to 0.48 Ϯ 0.21% ( p ϭ 0.05) in ␣-A␤-treated mice. Progressive accumulation of ␤-amyloid in the vicinity of blood vessels can result in microhemorrhages, and some studies have linked immunotherapy to an initial increase in CAA and microhemorrhages (Pfeifer et decrease during longer treatment periods (Schroeter et al, 2008). To exclude that the ␣-A␤ antibody treatment used here decreased parenchymal A␤ plaques but increased vascular A␤ deposits, we quantified CAA visualized by ThioS staining.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies of both active and passive A␤ immunization in transgenic mice have confirmed that removal of existing A␤ plaques can occur, sometimes within a matter of days, and this is associated with cognitive benefits (Schenk et al, 1999;Janus et al, 2000;Morgan et al, 2000;Schenk, 2002;Wilcock et al, 2004;Boche et al, 2008). However, several studies have demonstrated an increased incidence of cerebral microhemorrhages ex vivo in aged transgenic mice after a period of immunotherapy (Pfeifer et al, 2002;Racke et al, 2005;Wilcock et al, 2007;Schroeter et al, 2008;Thakker et al, 2009). The discontinued phase II active im-munization trial with aggregated A␤ as an immunogen (AN1792) observed more severe CAA in immunized patients than those without at a similar stage of AD, with multiple cortical hemorrhages in one case (Boche et al, 2008;Thakker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although detection of small (20 -400 M), individual microhemorrhages postmortem in mouse brain is possible by histological examination using Prussian blue (Pfeifer et al, 2002;Racke et al, 2005;Wilcock et al, 2007), it is very time consuming (Pfeifer et al, 2002;Wilcock et al, 2004;Racke et al, 2005;Schroeter et al, 2008). Two further fundamental questions cannot be easily addressed by using the ex vivo approach: 1) When do the microhemorrhages occur during immunotherapy?…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies in transgenic mice that generate a surplus of Ab demonstrated that antibodies directed against Ab N-terminus are able to enter the brain and decrease amyloid deposits in brain tissue and cerebral vasculature [61,62]. Moreover, such antibodies inhibit the synaptotoxic actions of Ab oligomers and enhance cognitive skill in APP transgenic mice [63,64].…”
Section: Recent Insights Into the Dementia Epidemicmentioning
confidence: 99%